Transplacental metastasis of malignant melanoma. - Bonifazi, E.; Ferrante, M.; Berloco, A.; Bellomo, G.; Ciampo, L. (European Journal of Pediatric Dermatology, 2001)
Malignant metastasising tumors of the pregnant woman usually do not metastasise to the fetus. Although melanoma is not the most frequent malignant tumor in pregnancy, the cases of fetal metastatic melanoma are more frequent as compared with all the other malignant tumors. Five cases of the relevant literature are reviewed and the pathogenetic mechanisms of this exceptional experiment of the nature are discussed.